2018
DOI: 10.1186/s11658-018-0108-y
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-DC regulates cellular turnover and the HBV-induced immune response by TLR9/STAT3 signaling in dendritic cells

Abstract: BackgroundLnc-DC is a specific group of long non-coding (Lnc) RNAs in dendritic cells (DCs). Its function has been previously studied, and includes roles in dendritic cell differentiation and the progression of some diseases. In this study, we observed the critical role of Lnc-DC in regulating the differentiation, growth, and apoptosis of dendritic cells.MethodsWe first isolated peripheral blood mononuclear cells to culture and induce into DCs, which were then co-cultured with hepatitis B virus (HBV)-secreting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 22 publications
(18 reference statements)
0
24
0
Order By: Relevance
“…It has been confirmed that LncRNAs exert a great function in a variety of cancer biology, 21 and affect tumor progression by regulating cell cycles and immune responses. 22 MALAT1 expression has been determined to upregulate in various tumors. Moreover, this gene can affect the proliferation, migration, invasion, and apoptosis of tumor cells, so it is considered as a potential biomarker for diagnosing or predicting cancers and as a therapeutic target for treating specific tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that LncRNAs exert a great function in a variety of cancer biology, 21 and affect tumor progression by regulating cell cycles and immune responses. 22 MALAT1 expression has been determined to upregulate in various tumors. Moreover, this gene can affect the proliferation, migration, invasion, and apoptosis of tumor cells, so it is considered as a potential biomarker for diagnosing or predicting cancers and as a therapeutic target for treating specific tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enhancing STAT3 activation, WFDC21P possibly participates in the regulation of STAT3 signaling. [54,55] As a regulator of WFDC21P, miR-4293 could further elevate STAT3 phosphorylation. Moreover, by regulating STAT3 activation, WFDC21P could elevate the expression of miR-4293.…”
Section: Discussionmentioning
confidence: 99%
“…The sustained activation of STAT3 induced by the phosphorylation of tyrosine residue 705 promotes the expression of genes involved in dendritic cell differentiation . lncRNA ‐DC is also implicated in the immune response to HBV and acts by reducing the concentration of secreted TNF‐α, IL‐6, IL‐12, and IFN‐γ, as well as increasing the IL‐1β concentration in dendritic cells …”
Section: Regulation Of Viral Replication By Lncrna‐mediated Innate Immentioning
confidence: 99%